Search for supersymmetric Higgs bosons in the di-tau decay mode in pp̄ collisions at s=1.8TeV - Acosta, D; Affolder, T; Albrow, MG; Ambrose, D; Amidei, D; Anikeev, K; Antos, J; Apollinari, G; Arisawa, T; Artikov, A; Ashmanskas, W; Azfar, F; et al. (2005)
A search for the direct production of Higgs bosons in the di-tau decay mode is performed with 86.3±3.5pb-1 of data collected with the Collider Detector at Fermilab during the 1994-1995 data taking period of the Tevatron. We search for events where one tau decays to an electron plus neutrinos and the other tau decays hadronically. We perform a counting experiment and set limits on the cross section for supersymmetric Higgs boson production where tan β is large and mA is small. For a benchmark parameter space point where mA0=100GeV/c2 and tan β=50, we limit the production cross section multiplied by the branching ratio to be less than 77.9 pb at the 95% confidence level compared to the theoretically predicted value of 11.0 pb. This is the first search for Higgs bosons decaying to tau pairs at a hadron collider. © 2005 The American Physical Society.